5x+8+48=11x+6

Simple and best practice solution for 5x+8+48=11x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+8+48=11x+6 equation:



5x+8+48=11x+6
We move all terms to the left:
5x+8+48-(11x+6)=0
We add all the numbers together, and all the variables
5x-(11x+6)+56=0
We get rid of parentheses
5x-11x-6+56=0
We add all the numbers together, and all the variables
-6x+50=0
We move all terms containing x to the left, all other terms to the right
-6x=-50
x=-50/-6
x=8+1/3

See similar equations:

| 3(4g+6=2(6g+9) | | 3x+10=47 | | y-3.7=4.2 | | 5x+6-3x+10=12-4x+2x | | 2x-5(x-9)=1 | | 3x²-5=2x | | 17=y-12 | | 2(x+5)/5=1+3+5x/4 | | 2x-5(x-9=1 | | P=2,320(1.2)x | | 3a=-3.5a | | 3a=3.5a | | -32+b=20 | | 7*x/3=8 | | 2x+2(-7+4x)=1-x | | d=|300−48| | | -2=y=9 | | -6h+7)+8=-19 | | 5000+x=3000 | | -41-6x=-x+19 | | 6/5v+2/9+7/4v=43/12(v+11/2)+57/11(3/4v+1 | | 4(1/3x-1/4)+4/3x+1=6 | | 7-x+3=9x+0 | | 5x+8+4x=11x+6 | | -6(-3x-3)+2=110 | | -1+3x=3x-1 | | 8(x+4)=-8(x+4) | | 6x-4=23-3 | | 7a-16=21a+24+28a+8 | | 7=5x-4x+5 | | 6+9x=10+8x | | 8x+12=3x+6 |

Equations solver categories